Effects of 20-s and 180-s double poling interval training in cross-country skiers - Nilsson, J. E.; Holmberg, H. C.; Tveit, P.; Hallen, J. (European Journal of Applied Physiology, 2003)
The purpose of this study was to investigate the effect of upper body 20-s or 180-s interval training, using a double poling ergometer, on upper body power output and selected physiological and biomechanical parameters in cross-country skiers. Twenty (12 male, 8 female) well-trained cross-country skiers took part. Two intervention groups, a 20-s interval training group (IT20; n=6) and a 180-s interval training group (IT180; n=7), underwent training three times a week for 6 weeks on a double poling ergometer. A third group served as a control (CON; n=7) and followed the same training program as the IT20 and IT180 groups without the double poling ergometer interval training. The IT20 and IT180 groups significantly (P<0.05) increased both peak and mean power in a 30-s test and mean power in a 6-min test after double poling training. There was a significant improvement in work efficiency in both IT20 and IT180 (P<0.05) and, in IT180, a significant reduction (P<0.05) in blood lactate concentration at given sub-maximal workloads. O2peak increased significantly during double poling in IT180 (P<0.05) only. O2max did not change significantly in either group. There were no significant changes in any of the test variables in CON. In conclusion, this study shows that 6 weeks of 20-s or 180-s double poling interval training, three times a week, significantly increases power output in both 30-s and 6-min tests, as well as in selected physiological and biomechanical parameters in well-trained cross-country skiers.